FROM SUBTITLES TO SPEAKING: “HOW DIGITAL MEDIA NATURALLY HELPED ME MASTER ENGLISH” - Turgunova Shokhsanam Alisherovna; Khahhorova Fotima (Bright Mind Publishing, 2025)
When we think about learning English, most people imagine textbooks, grammar exercises, and classroom lessons. But for me, the real progress started somewhere else — in my headphones and on my screen. Watching K-dramas with subtitles, listening to English music, and spending time on YouTube became more than just entertainment. They turned into powerful learning tools. Through these daily exposures, I started to read faster, understand spoken English better, and even speak more fluently without much pressure. To explore whether others have had a similar experience, I asked several classmates how they learn English outside school. Their answers revealed that I wasn’t the only one using media as a learning method — many had found similar benefits in music, films, and online content.